Elusive alpha and beta control in a multicausal world - Fiedler, Klaus (Basic & applied social psychology, 2020)
Virtually all scientific outlets, including the most prestigious journals, have implemented strict rules of α and (1-β) control, supposed to quantify the probability of a significant result assuming H0 and H1, respectively. However, estimation of α and β rests on the untenable assumption that a systematic effect ΔY in the dependent variable cannot be brought about by any other causal influence than the influence ΔX stated in H1 and negated in H0. Yet, in a given study, empirical evidence on ΔY related to ΔX can always reflect extraneous causal influences, because no treatment or measurement tool affords a pure measure of X and Y, respectively. Consequently, α and β cannot quantify error probabilities in specific studies.